A systematic review of the relationship between the distributions of aggrecan gene VNTR polymorphism and degenerative disc disease/osteoarthritis. Issue 4 (April 2018) - Cong, L.; Tu, G.; Liang, D.
Abstract : Objectives: Degenerative disc disease (DDD) and osteoarthritis (OA) are relatively frequent causes of disability amongst the elderly; they constitute serious socioeconomic costs and significantly impair quality of life. Previous studies to date have found that aggrecan variable number of tandem repeats (VNTR) contributes both to DDD and OA. However, current data are not consistent across studies. The purpose of this study was to evaluate systematically the relationship between aggrecan VNTR, and DDD and/or OA. Methods: This study used a highly sensitive search strategy to identify all published studies related to the relationship between aggrecan VNTR and both DDD and OA in multiple databases from January 1996 to December 2016. All identified studies were systematically evaluated using specific inclusion and exclusion criteria. Cochrane methodology was also applied to the results of this study. Results: The final selection of seven studies was comprehensively evaluated and includes results for 2928 alleles. The most frequent allele among all the studies was allele 27. After comparing the distributions of each allele with others, statistically significant differences have been found in the distribution of the alleles by the two groups, with an over-representation of allele (A)21 (disease: 3.22%, control: 0.44%). Thus, carrying A21 increased the risk of DDD. Such an association was not found to be statistically significant when considering the risk of OA. Conclusions: The findings suggest that VNTR A21 seems to be associated with higher risk to DDD, however, such an association may not be statistically significant regarding the risk of OA. Cite this article : L. Cong, G. Tu, D. Liang. A systematic review of the relationship between the distributions of aggrecan gene VNTR polymorphism and degenerative disc disease/osteoarthritis. Bone Joint Res 2018;7:308–317. DOI: 10.1302/2046-3758.74.BJR-2017-0207.R1